2021
DOI: 10.1504/ijsn.2021.117887
|View full text |Cite
|
Sign up to set email alerts
|

Impact of post-quantum hybrid certificates on PKI, common libraries, and protocols

Abstract: In this work, we assessed the impact of post-quantum (PQ) cryptography on public key infrastructure (PKI). First, we modified a commercially available certification authority (CA) to issue 'hybrid' certificates (X.509 certificates with PQ extensions). Then we assessed the impact of using these certificates on some existing protocols, including TLS, OCSP, CMP, and EST, with open-source libraries OpenSSL and CFSSL, and with a commercially available cryptographic toolkit. We found that most of the protocols and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The X.509v3 construction using any of these post-quantum algorithms makes the certificate too voluminous that it exceeds the link MTU size and subsequently, leads to the IP fragmentation issues and causes slow network performance respectively. This case gets worse if hybrid certificates need to be constructed with post-quantum algorithms as well as legacy public key algorithms like elliptic curve cryptography (ECC) or Rivest-Shamir-Adleman (RSA) algorithms are used to achieve backward compatibility with the X.509v3 certificates [35]. It is noteworthy that the hybrid certificates are required for smoother migration from legacy to post-quantum and quantum-safe certificates though it comes with the heavy cost of poor network performance due to exceeding standard MTU size of the underlying link layer.…”
Section: Capability Review Of X509v3 Withmentioning
confidence: 99%
“…The X.509v3 construction using any of these post-quantum algorithms makes the certificate too voluminous that it exceeds the link MTU size and subsequently, leads to the IP fragmentation issues and causes slow network performance respectively. This case gets worse if hybrid certificates need to be constructed with post-quantum algorithms as well as legacy public key algorithms like elliptic curve cryptography (ECC) or Rivest-Shamir-Adleman (RSA) algorithms are used to achieve backward compatibility with the X.509v3 certificates [35]. It is noteworthy that the hybrid certificates are required for smoother migration from legacy to post-quantum and quantum-safe certificates though it comes with the heavy cost of poor network performance due to exceeding standard MTU size of the underlying link layer.…”
Section: Capability Review Of X509v3 Withmentioning
confidence: 99%
“…This message contains signatures of both ECDSA (M sgSig E ) and PQC (M sgSig P ), implying that the message format is also extended to carry the second signature. This type of hybrid certificate based on X.509 to address migration toward PQC algorithm has already been tested and verified to work for TLS, OCSP and other protocols [16], [27]. Fig.…”
Section: A Absence Of Forward Compatibilitymentioning
confidence: 99%
“…Alnahawi et al [2] present comprehensive coverage of PQC and their issues such as downgrade attack. Fan et al [16] discuss their experiment of hybrid certificates on protocols such as TLS1.2, OCSP, CMP, and EST, and showed that most of the protocols and libraries worked with hybrid certificates using X.509 certificate with post-quantum extensions. Yunakovsky et al [30] recommend using hybrid cryptographic schemes using current and postquantum solutions for PKI against attacks using quantum computers.…”
Section: )mentioning
confidence: 99%